Zum Stand der Radikalisierungsprävention im Phänomenbereich des Islamismus - Mehmet Kart; Margit Stein; Yannick von Lautz; Eike Bösing; Veronika Zimmer; Petra Rother; Caner Ayyildizt (IUBH Internationale Hochschule, 2021)
– The scientific analysis of the phenomenon of Islamist radicalization processes in adolescence is of high complexity. Particularly after the attacks on September 11, 2001, and later on due to the media propaganda of radical Islamist terrorist groups such as the so-called Islamic State, the topic of Islamic radicalization gained more and more momentum. Also in Germany radical Islamic groups spread a religiously based radical ideology. According to the report on protection of the constitution, 2018 (Verfassungsschutzbericht 2018) more than 1.000 people from Germany have joined jihadists in Syria and Iraq since 2012. However, the number of unreported cases is probably higher. International research is intensively concerned with the psychological, social, religious, and political causes, forms, and development processes of Islamist deradicalization. Processes of distancing and deradicalization of young people and possibilities to prevent radicalization have increasingly been in the focus of political debates in Germany in recent years. In this context, it is primarily important to understand how young people distance themselves from extremist ways of thinking and acting and what role established prevention measures such as counseling centers as well as families, peer groups, schools, workplaces, and religious institutions play in this process of deradicalization. This article deals with current discourses of distancing and deradicalization in the phenomenon area of Islamist radicalization and presents the BMBF-funded project "Distanz". The aim of the project "Distanz" is to provide a comprehensive scientific analysis of the process of deradicalization and successful distancing from Islamist radicalization and to develop preventive pedagogical approaches for educational professionals.
Keywords: 300; Deradicalization; radicalization; extremism; Islam; prevention